Concordance between laparoscopic diagnosis and pathological diagnosis in ovarian endometriosis with deep infiltrating endometriosis - LI Xiao, GUO Hongling, JIANG Hongye, MA Ying (Xin yixue)
Objective To explore the coincidence rate between laparoscopic diagnosis and pathological diagnosis of ovarian endometriosis （OEM） combined with deep infiltrating endometriosis （DIE）. Methods The clinical data of 304 patients with OEM combined with DIE were retrospectively analyzed. They all used OEM as the surgical indication. DIE lesions were found during laparoscopic surgery. The distribution of DIE during the operation was observed， including distribution locations and distribution characteristics， and compared. The coincidence rate between laparoscopic diagnosis of DIE lesions in different parts and pathological diagnosis. Results In 304 OEM patients with DIE， a total of 995 DIE lesions were removed during laparoscopic surgery， of which 489 （49.2%） were located in the sacral ligament， followed by： a total of 131 lesions （13.2%） in the cervicovaginal and rectal space and surrounding areas， 93 rectosigmoid lesions （9.4%）， and 66 ureteral lesions （6.6%）. Pathological diagnosis showed endometrial stroma and glands in 788 cases， with a pathological coincidence rate of 79.2% （788/995）. Among them， the diagnostic coincidence rate of intestinal wall lesions was the highest， reaching 100%， and the diagnostic coincidence rate of sacral ligament was 77.7%， the ureteral endometriosis lesions were 81.8%. Compared with pathological diagnosis， the positive predictive value of laparoscopic diagnosis of DIE was 79.2% （788/995）， sensitivity was 79.2% （788/995）， negative predictive value was 85.0% （17/20）， and spectificity was 7.9% （17/224）. ConclusionThe coincidence rate between laparoscopic diagnosis of DIE and pathological diagnosis is high. OEM is often associated with DIE lesions， and DIE lesions can be diagnosed and removed during laparoscopic surgery.